2023
DOI: 10.1101/2023.06.09.544380
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell RNA sequencing identifies response of renal lymphatic endothelial cells to acute kidney injury

Abstract: The inflammatory response to acute kidney injury (AKI) likely dictates future renal health. Lymphatic vessels are responsible for maintaining tissue homeostasis through transport and immunomodulatory roles. Due to the relative sparsity of lymphatic endothelial cells (LECs) in the kidney, past sequencing efforts have not characterized these cells and their response to AKI. Here we characterized murine renal LEC subpopulations by single-cell RNA sequencing and investigated their changes in cisplatin AKI. We vali… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…In this issue of JASN , Creed et al provide additional insights into the implications of lymphatic biology for kidney diseases. 3 By exploring the altered gene expression changes in response to cisplatin-induced AKI in male mice, the investigators identified the lymphatic endothelial cells (LECs) molecular signature as being most consistent with vascular endothelial growth factor receptor signaling, T-cell differentiation, and regulation of inflammatory response, supporting the notion that LECs respond to AKI by undergoing lymphangiogenesis and upregulating their interactions with immune cells. In addition, by comparing the molecular responses of LECs to distinct injury stimuli (cisplatin versus ischemia–reperfusion injury), the investigators revealed that the response of LECs is likely influenced by the specific mode and context of injury, thereby substantiating the existing evidence of conflicting outcomes in the literature across different models.…”
mentioning
confidence: 91%
“…In this issue of JASN , Creed et al provide additional insights into the implications of lymphatic biology for kidney diseases. 3 By exploring the altered gene expression changes in response to cisplatin-induced AKI in male mice, the investigators identified the lymphatic endothelial cells (LECs) molecular signature as being most consistent with vascular endothelial growth factor receptor signaling, T-cell differentiation, and regulation of inflammatory response, supporting the notion that LECs respond to AKI by undergoing lymphangiogenesis and upregulating their interactions with immune cells. In addition, by comparing the molecular responses of LECs to distinct injury stimuli (cisplatin versus ischemia–reperfusion injury), the investigators revealed that the response of LECs is likely influenced by the specific mode and context of injury, thereby substantiating the existing evidence of conflicting outcomes in the literature across different models.…”
mentioning
confidence: 91%